Zaroiło się od Grottgera… - BRYL, Mariusz (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2013)
The author reflects on the poor historical consciousness of contemporary Poles, determined to a large degree by the present condition of the Polish State, which, after 1989, adopted a hybrid political system defi ned as the Third Republic of Poland. Whereas the communist period in Poland was a time of great value transformation undertaken in order to produce the new Soviet Polish nation, an atomized human mass deprived of a common cultural code, the transformation of the political system after 1989 did not bring a radical change of values. One might see a deep contrast in this respect between the years following 1918, when the Second Republic of Poland came into being after a period of captivity, and 1989. In the Second Republic of Poland, the cult of the January Insurrection of 1863 became part of the offi cial ideology of the State, and the veterans of that event received privileged placed during patriotic celebrations. By contrast, the political elites of the Third Republic of Poland have anathemized the invincible soldiers who fought for the independence of our country in the anti-Soviet insurrection after 1944, having accused them of nationalism and anti-Semitism. It might even seem that a change in this opinion, prevailing among the political elites in today’s Poland, might cause their annihilation. In the second part of the essay the author describes the myth-inspiring infl uence of Artur Grottger’s works, rooted in their heroic visual structure, and referring to his book Cykle Artura Grottgera. Poetyka i recepcja [“Artur Grottger’s Cycles: The Poetics and the Reception”] of 1994, wonders whether the frequent references to Grottger’s works on the 150th anniversary of the January Insurrection proved that they still provide loci communes for the Poles, as was the case in 1981 (the author refers to the shocking testimony of a miner from the “Wujek” mine). It seems though that the process of the destruction of Polish national memory and consciousness in the years following the «Round Table Talks» in Poland was much more acute than the similar process that had taken place during the period of communism, and thus it is hard to assume that a common identity of the Poles, based on the loci communes provided by Grottger’s works, is still possible. In the concluding part of the essay the author points that fi lm is the medium which opens a possibility for creating works of art of myth-inspiring nature that might contribute to the constitution of the identity of the Polish nation. Since myth is rooted in factual truth, the author holds that documentaries might currently become a fi eld of demystifi cation, stimulating Polish national memory. Only on such «soil,» in favorable political conditions, may feature movies consolidating Polish identity be made in the future. Translated by Dorota Chabrajska